2007
DOI: 10.1124/jpet.107.128280
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Proof of Mechanism and Pharmacokinetics and Pharmacodynamic Relationship with 4′-Cyano-biphenyl-4-sulfonic Acid (6-Amino-pyridin-2-yl)-amide (PF-915275), an Inhibitor of 11β-Hydroxysteroid Dehydrogenase Type 1, in Cynomolgus Monkeys

Abstract: Glucocorticoids, through activation of the glucocorticoid receptor (GR), regulate hepatic gluconeogenesis. Elevated hepatic expression and activity of 11␤-hydroxysteroid dehydrogenase type 1 (11␤HSD1) play a key role in ligand-induced activation of the GR through the production of cortisol. Evidence from genetically modified mice suggests that inhibition of 11␤HSD1 might be a therapeutic approach to treat the metabolic syndrome. We have identified a potent 11␤HSD1 inhibitor, 4Ј-cyano-biphenyl-4-sulfonic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…Selective 11β-HSD1 inhibitors decrease local glucocorticoid generation in rodent and primate models and in humans [39][40][41]. To date, clinical efficacy has only been demonstrated in rodents, which showed improved glucose tolerance and lipid profiles, as well as increased insulin sensitivity and decreased atherogenesis [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Selective 11β-HSD1 inhibitors decrease local glucocorticoid generation in rodent and primate models and in humans [39][40][41]. To date, clinical efficacy has only been demonstrated in rodents, which showed improved glucose tolerance and lipid profiles, as well as increased insulin sensitivity and decreased atherogenesis [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…So far, to our knowledge, there are no reports of PF-915275 activity in patients with T2DM or MetSyn (or any of the associated components). Bhat et al showed, in normal cynomolgus monkeys, that PF-915275 dose-dependently inhibits 11 -HSD1-mediated conversion of prednisone to prednisolone and reduces insulin levels (Bhat et al, 2008). Hollis et al reviewed the clinical results obtained with the selective 11 -HSD1 inhibitor INCB13739.…”
Section: Human 11β-hsd1 Inhibition Studiesmentioning
confidence: 99%
“…11 -HSD2 is expressed principally in the distal nephron, where it inactivates cortisol to cortisone and thereby protects MR from cortisol (Andrews et al, 2003;Edwards et al, 1988;Ferrari, 2010;Funder et al, 1988;Palermo et al, 2004). PF-915275 is a potent and selective 11 -HSD1 inhibitor, without adverse side effects in a wide range of orally tested doses, that is selective for the human and primate enzymes (Bhat et al, 2008;Courtney et al, 2008). A modest pharmacodynamic effect of PF-915275 on 11 -HSD1 activity in the healthy human liver is reported, but experiments to assess its inhibitory effect in the AT have not been performed (Courtney et al, 2008;Hollis & Huber, 2011).…”
Section: Human 11β-hsd1 Inhibition Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Some clinical candidates, such as INCB-13739 and PF-915275, lack potency against rodent enzyme, so in vivo pharmacokinetics (PK)/PD studies of these compounds require primate models. 16 In our series, cross-species potencies of adamant-2-yl derivatives 4d and 4e allowed us to employ rodent model.…”
mentioning
confidence: 99%